Physico-Chemical and Bacteriological Investigation on the River Cauvery of Kollegal Stretch in Karnataka - Venkatesharaju, K; Ravikumar, P; Somashekar, RK; Prakash, KL (Kathmandu University Journal of Science, Engineering and Technology, 2010)
Cauvery River is the major river system of south India was studied for 19 prime physicochemical and 2 bacteriological parameters at six locations of the Kollegal stretch, for a period of Two years (2006–2008) at monthly intervals. Over the years of time, river has been subjected to human interference regularly and water quality was to be getting deteriorated profoundly. Major anthropogenic activities practiced in and around the stretch: agriculture, abstraction of water for irrigation and drinking, washing cloths and utensils, discharging of sewage waste, sand dredging, boating, fishing, open defecation and religious ritual activities along the stretch were generating serious threat to the biota of the river by altering the physicochemical and biological concentration of the river system. The seasonal and yearly trends were discussed to comprehend anthropogenic interferences on the river stretch. Correlation analysis was also been tried in between physico-chemical parameters. The pH, Conductance, Alkalinity and Hardness levels indicate the moderate quality of water. The values of DO, BOD and COD levels indicate the absence of major organic pollution sources. Seasonal and yearly averages of plant nutrients like phosphate, nitrates, potassium and also sulphates at drain out falls and mixing zones, were not showing any significant variation in their concentration indicate no sign of problems like eutrophication, which is generally raise due to agricultural and sewage wastes. The other possibility is that since there are no major industries in the project area, the major source of organic pollutants is only the domestic source. Population density spread over sparsely located villages like Dasanapura and Harle certainly contributes towards total and fecal coliforms as excreta of the villagers due to lack of toilets in their houses. Thus present study concludes that river water was not polluted; all results are within permissible limit when compared with Bureau of Indian Standards (BIS) and National River water quality standards. DOI: 10.3126/kuset.v6i1.3310 Kathmandu University Journal of Science, Engineering and Technology Vol.6(1) 2010, pp50-59